The use of nephrometry scoring systems can help urologists predict the risk of conversion to radical nephrectomy in patients scheduled for partial nephrectomy - Ficarra, Vincenzo; Rossanese, Marta; Giannarini, Gianluca; Crestani, Alessandro; Simonato, Alchiede; Inferrera, Antonino (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Conversion to radical nephrectomy (RN) in patients scheduled for partial nephrectomy (PN) is an important outcome that should be strongly considered during the decision-making process and adequately discussed with patients during their preoperative counseling. This unplanned event could be due to severe intraoperative complications or oncologic reasons. Intraoperative suspicion of hilar and/or perirenal fat tissue involvement, peritumoral venous involvement, tumor multifocality and/or iatrogenic rupture of the tumor are the most common conditions threatening the oncological safety of the procedure.